PERAN KECAMATAN DALAM EVALUASI DANA DESA LADARA DI KECAMATAN TUHEMBERUA KABUPATEN NIAS UTARA (STUDY KASUS DESA LADARA) - AMIRSAN PUTRA CANIAGO; AYLER BENIAH NDRAHA; YASMINAR TELAUMBANUA (LP2MTBM MAKARIOZ, 2022)
According to the Village law, Village funds are defined as funds sourced from the APBN which are beneficial for the Village which are transferred through the Regency/City APBD and are used to finance government administration, development implementation, community development and community empowerment. The purpose of this study is to describe the accountability of the evaluation of the management of the Village Fund Allocation which consists of several stages, namely the planning stage, the disbursement and distribution stage, the use stage, the supervision stage, and the accountability of the Village Fund Allocation. This study uses a descriptive qualitative case study approach with the research location in 1 Ladara village, Tuhemberua sub-district. Data was collected through observation, interviews, and documentation to obtain the validity of the data. The results of the study are the importance of the role of the sub-district head in evaluating village funds, especially in Ladara village, Tuhemberua sub-district, North Nias district